Biosorption of copper by water hyacinth roots - Low, K.S.; Lee, C.K.; Tai, C.H. (Taylor & Francis Group, 1994)
Biomass of non-living dried water hyacinth roots, Eichhornia crassipes, showed high sorption for copper from aqueous solutions. Maximum sorption was 20.90 mg Cu/g as determined from Langmuir isotherm. Several factors affecting sorption were investigated. They include effect of pH, initial concentrations, presence of chelators and other metals. The feasibility of removing copper from electroplating waste using this material in a packed-bed system was also discussed.